Buhari : the PTF years (collected speeches) - Adamu, Adamu (Ibadan : Spectrum Books, 1999)
A collection of speeches made by the chief executive of the (Petroleum (Special) Trust Fund PTF), Major-General Muhammadu Buhari (rtd) between August 1995 and August 1998.
Includes speeches delivered by General Muhammadu Buhari between August 1995 and August 1998, in his capacity as chairman of the Petroleum (Special) Trust Fund, Nigeria.
oif 25/02/15
Loan
Keywords: Special funds; Economic development; PTF; Nigeria